Improving salinity tolerance of alfalfa (Medicago sativa L.) through conventional breeding - Cornacchione, Monica; Odorizzi, Ariel; Basigalup, Daniel Horacio; Arolfo, Valeria (INTA, 2024)
Poster y resumen